1973
DOI: 10.1172/jci107218
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Mechanisms of Cerebral Edema in Diabetic Comas. EFFECTS OF HYPERGLYCEMIA AND RAPID LOWERING OF PLASMA GLUCOSE IN NORMAL RABBITS

Abstract: A B S T R A C T To investigate the pathophysiology of cerebral edema occurring during treatment of diabetic coma, the effects of hyperglycemia and rapid lowering of plasma glucose were evaluated in normal rabbits. During 2 h of hyperglycemia (plasma glucose = 61 mM), both brain (cerebral cortex) and muscle initially lost about 10% of water content. After 4 h of hyperglycemia, skeletal muscle water content remained low but that of brain was normal. Brain osmolality (Osm) (343 mosmol/kg H20) was similar to that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
1

Year Published

1974
1974
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(68 citation statements)
references
References 39 publications
2
65
1
Order By: Relevance
“…High doses of insulin may also be a risk factor for cerebral oedema, as indicated by animal models [26,27] and supported by our observational studies. Finally, the dangers inherent in using large volumes of relatively dilute fluids have been highlighted by many studies [5,7,17].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…High doses of insulin may also be a risk factor for cerebral oedema, as indicated by animal models [26,27] and supported by our observational studies. Finally, the dangers inherent in using large volumes of relatively dilute fluids have been highlighted by many studies [5,7,17].…”
Section: Discussionsupporting
confidence: 83%
“…Finally, the dangers inherent in using large volumes of relatively dilute fluids have been highlighted by many studies [5,7,17]. It is compatible with the 'idiogenic osmole' hypothesis of cerebral oedema risk, where relatively 'dilute' fluids may cross the blood-brain barrier more easily when the intracerebral osmolality is increased [26,28].…”
Section: Discussionmentioning
confidence: 84%
“…Group I: effects of acute untreated hypernatraemia on brain adaptation In preliminary studies on conscious rabbits, not reported here, it was noted that infusion of hypertonic NaCl (1-7 M) sometimes resulted in slowing of respiration. Therefore, all of these experiments were performed on rabbits that were anaesthetized, paralysed and artificially ventilated (Arieff, Kleeman, Keushkerian & Bagdoyan, 1973). Briefly, twelve control and nine experimental rabbits, which were to be made acutely hypernatraemic (see below), were fasted overnight.…”
Section: Studies In Rabbitsmentioning
confidence: 99%
“…After removing the rabbit from the box, it was placed on a heating blanket (37°C) and tracheostomized. A 20 gauge catheter (Angiocath; Quinton Instrument Company, Bothell, WA, USA) was inserted into the ear artery and attached to a strain gauge transducer (Statham) via a tap so that arterial blood pressure and heart rate could be continuously recorded on a strip chart recorder (Statham) and to allow blood samples to be removed every hour for arterial blood gas analysis (Arieff et al 1973). As previously described (Arieff et al 1974b), paralysis was induced with succinylcholine (20 mg kg-' i.v.)…”
Section: Studies In Rabbitsmentioning
confidence: 99%
“…The brain generates intracellular osmolytes as a protective mechanism (8). Osmolytes are organic solutes that are essential for cell-volume homeostasis and they may also function as general protectors for brain cells.…”
Section: Discussionmentioning
confidence: 99%